STRATEGI KOMUNIKASI SANGGAR TARI JEJAMA DALAM MELESTARIKAN SENI BUDAYA TARI LAMPUNG - Lumbu, Aliyandi; Widodo, Anton; Dwi Nopriyana, Rahma (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2024)
This research is an effort to discover and introduce Lampung culture or customs, one of which is Lampung traditional dance. This dance studio is used by Lampung tribal residents in the sub-district as a forum for communicating and staying in touch. This research uses qualitative research methods in which data is in the form of words obtained through interviews, observation and documentation and then analyzed. The aim of this research is to find out about how Sanggar Jejama's communication strategies work in an effort to preserve Lampung cultural traditions. The results of the research are that awareness of the importance of preserving Lampung cultural customs as a legacy from our ancestors means that studios, especially dance studios, are needed as a communication medium to introduce Lampung cultural traditions so that they are not destroyed or lost.